Analysis of the Growth Rate of Seaweed (Kappaphycus alvarezii) with the Longline Method Using Tissue Culture Seed Results in Tual City - Ngangun, Amina; Heriansah, Heriansah; Idrus, Muh. Ikhsan (LPPM Institut Teknologi dan Bisnis Maritim Balik Diwa, 2025)
The availability of K. Alvarezii seaweed seeds in terms of adequate quantity, quality and continuity is one of the fundamental problems for the development of its cultivation. This study aims to determine the growth rate of seaweed tissue culture seeds, K. alvarezii with treatment on local seeds. Seaweed seedlings after being weighed are planted using the long line method and measured in weight after 30 days of maintenance. Sampling of water quality parameters is carried out every week periodically. At the end of the maintenance period, weighing is carried out to determine the absolute weight growth, daily weight and daily specific growth. The data from weighing and observation were analyzed descriptively, quantitatively, and qualitatively. The results obtained showed excellent growth and almost uniform seed size in tissue culture seed yields. All water quality parameters are in the decent to optimal range. Tissue culture seeds are considered suitable for development in the waters of Fiditan Village, North Dullah Island District, Tual City.